(3eLed GddZIs - (3GHf aGQS , CHh GdMSjf CMeO Hf aGQS Hf RcQjGA GdbRhjfj GdQGRj,J (B395 (3g` s ((3CHh eVQ GdYbdi eMeO Hf CMeO Hf eMeO ZjGK s)
(3ChdgG (B:s
(3GdMeO ddg MeOkG JbJVjg fYeg GdOGFeI Efi deG TGgOJ cJGH GdYjf cJGH GdLegQI SejJg eLed GddZI dCfi CLedJ GdcdGe ajg ELeGdkG CNQLJg Ydi MQha GdeYLe cJGH GdCda s
(3BNQgG (B:s
(3dCf GdjGA EfeG jYJHQ HgG ai gPjf GdHGHjf GdMQa GdPi HYOgeG (B: (3hbO eVi cdg ai CHhGH GdcJGH Je GdcJGH eLed GddZI s
(3fSNI NGeSIs
(3bQf GdfSN (B:s
(3GdbQf GdNGeSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B193 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B40s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdChd (B- (3bSe GdKGfi (B- (3U (B203 s
Keywords: (3GddZIs